Improving Recycled Waste Management Performance in Ngaliyan District, Semarang City - Prihanita Ratih Fitriandani; Mochtar Hadiwidodo; Haryono Setiyo Huboyo (Universitas Diponegoro, 2022)
The waste that enters the Jatibarang landfills does not go through the management and processing process in advance, and the people's laziness in sorting waste has resulted in an increase in waste at the Jatibarang landfills. Ngaliyan reduce, reuse, recycle (3R) waste management site is currently inactive due to a lack of implementation in aspects of waste management. Therefore, it is necessary to plan waste management as an effort to overcome urban waste by increasing performance at reduce, reuse, recycle (3R) waste management sites. Data collection methods used are sampling, interviews, and questionnaires. In this technical, operational planning of waste management, an area of reduce, reuse, recycle (3R) waste management site is required of 661 m2. Organic waste is processed through composting using the Open Windrow method, and inorganic waste is managed using the MRF (material recovery facility) method. The total cost required is IDR 11,135,856,300.00. The community is expected to be able to participate in waste processing and management through 3R-based sorting, comply with applicable regulations, and pay a retribution every month.